Benzylation of Toluene over Iron Modified Mesoporous Ceria - K. J. Rose Philo; Sugunan Sugunan (Bulletin of Chemical Reaction Engineering & Catalysis, 2012)
Green chemistry has been looked upon as a sustainable science which accomplishes both economical and environmental goals, simultaneously.With this objective, we developed an alternative process to obtain the industrially important benzyl aromatics by benzylation of aromatics using benzyl chloride, catalysed by mesoporous solid acid catalysts. In this work mesoporous ceria is prepared using neutral surfactant which helped the calcination possible at a lower temperature enabling a higher surface area. Mesoporous ceria modified with Fe can be successfully utilized for the selective benzylation of toluene to more desirable product methyl diphenyl methane with 100% conversion and selectivity in 2 hours using only 50mg of the catalyst under milder condition. The reusability, regenerability, high selectivity, 100% conversion, moderate reaction temperature and absence of solvent, etc. make these catalysts to be used in a truly heterogeneous manner and make the benzylation reaction an environment friendly one. © 2012 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)